Assessment of adoption and impact of management innovations in agriculture carbon project in East Africa - Khatri-Chhetri, Arun; Juma, Ogada Maurice; Wekesa, Amos; Recha, John W.M.; Radeny, Maren A.O. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This working paper presents results of an impact assessment of management innovations that were introduced in agricultural carbon projects in East Africa. We evaluated the effect of project design, management, and monitoring transfer of responsibilities to local communities on the performance of agricultural carbon projects. The assessment included the economic, social, and environmental impacts of the projects on the smallholder farmers. The agriculture carbon projects implemented by Vi Agroforestry and Environmental Conservation Trust (ECOTRUST) have received a total of 1,951,437 tCO2e greenhouse gas (GHG) emissions reduction credits from 2010 to 2019. In Vi Agroforestry, 29,500 farm households in 1,725 farmers groups benefited from the implementation of the projects. They received a total of 624,960 tCO2e GHG reduction credits in the last 10 years. Similarly, around 9,000 smallholder farmers participated in the agricultural carbon project managed by ECOTRUST and they received 1,326,447 tCO2e worth of verified emissions reduction certificates from 2010 to 2019. The majority of the farmers (~70%) in the agricultural carbon projects were women. This assessment showed that the institutional approach of transferring management authority to local communities, including capacity building activities and social inclusion, can generate multiple benefits (economic, social, and environmental) for the smallholder farmers. Local institutions (i.e., farmer groups) and intermediaries (i.e., non-governmental organizations) played a leading role in the use of management innovations (i.e., training manuals) for effective design, management, and monitoring of the agricultural carbon projects in Kenya and Uganda.